Answer:
No real solutions
Explanation:
0=x^2+6x+13
Step 1: Subtract x^2 from both sides.
0−x^2=x^2+6x+13−x^2
−x^2=6x+13
Step 2: Subtract 6x from both sides.
−x^2−6x=6x+13−6x
−x^2−6x=13
Step 3: Since the coefficient of -x^2 is -1, divide both sides by -1.
−x^2−6x/−1 = 13/−1
x^2+6x=−13
Step 4: The coefficient of 6x is 6. Let b=6.
Then we need to add (b/2)^2=9 to both sides to complete the square.
Add 9 to both sides.
x^2+6x+9=−13+9
x^2+6x+9=−4
Step 5: Factor left side.
(x+3^)2=−4
Step 6: Take square root.
x+3=±√−4
Step 7: Add -3 to both sides.
x+3+−3=−3±√−4
x=−3±√−4